ChemInform Abstract: In situ Generation of the Ohira—Bestmann Reagent from Stable Sulfonyl Azide: Scalable Synthesis of Alkynes from Aldehydes. Issue 12 (March 2015) - Jepsen, Tue Heesgaard; Kristensen, Jesper Langgaard
Abstract An improved method for the in situ generation of the Ohira—Bestmann reagent and its application for a scalable and convenient approach for the synthesis of alkynes from aldehydes is given.